EXPLORING THE DEPICTIONS OF CONVERSATION DOMINANCE IN ADONG’S SILENT VOICES. - Gada, Jemimah Dan’azumi (Igwebuike Journal: An African Journal of Arts & Humanities, 2025)
This paper investigates depictions of conversation dominance in selected conversations of the literary text- Silent Voices to underscore female dominance as evidenced in the use of commands, declaratives, and interrogatives. It is a qualitative study that employs Systemic Functional Linguistics (SFL) tools to analyse how the choices made in language reveal roles assumed by speakers in a conversation. Specifically, the mood system is explored to uncover dominance in mixed-gender conversations from the text. A purposive sampling technique is adopted to extract relevant excerpts from the study. The analysis reveals that females tend to use imperatives and declaratives more than their male counterparts. On the other hand, the males use more interrogatives (open interrogatives) demanding large chunks of information which typically signal dependence on the females for information thereby tagging the males as the controlled and the females as the controllers during the conversation. Even in their use of interrogatives, the females used more polar questions that tended to demand short answers, again portraying them as the controllers in the conversations. The study concludes that females too dominate males in conversations contrary to the popular stance by previous scholars that males are the controllers in mixed-gender conversations.